RESEARCH ACTIVITIES IN UKRAINIAN LANGUAGE AND LITERATURE LESSONS AS A MEANS OF SHAPING STUDENTS’ CORE COMPETENCIES - Olena V. Khomenko (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article discloses and describes the formation of research skills in the lessons of the Ukrainian language and literature, highlights the essence of research activities, presents the main definitions and formulates its own vision for the definition of this concept. A group of principles has been identified that meet the requirements of research work and contribute to the formation of research skills of students in the process of studying the Ukrainian language and literature. Based on the analysis of psychological and pedagogical literature and the author’s own pedagogical experience, the main methods are determined that contribute to the formation of analytical abilities among students, the ability to compare, classify and generalize information. The stages of organization of research work of students at the institutions of general secondary education by means of consistent integration of science and educational process are disclosed. One of the effective forms of conducting classes in the Ukrainian language and literature in the process of forming research skills is defined as a lesson-study. Its structure was submitted, the main stages were described. It has been proved that the use of elements of problematic, search, research, heuristic methods makes the learning process more productive. The development of students’ research skills helps to achieve certain goals: to raise students’ interest in learning and to motivate them to achieve better results.